Profile of Environmental Worldview in 10th-Grade Students of State Senior High School 1 Turen of Malang Regency - Rahman, Titis Irodatur; Sueb Sueb; Vivi Novianti (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2025)
Environmental worldview is a human paradigm towards the environment that describes how humans view and behave towards the environment. The research is to determine and analyze the environmental worldview of students at State Senior High School 1 Turen. This research was designed using a survey method involving 10th-grade students of State Senior High School 1 Turen, Malang Regency, using the New Ecological Paradigm (NEP) instrument. NEP is a concept in environmental sociology that describes a new perspective on the relationship between humans and nature. It has demonstrated validity (r count > r table = 0.219) and reliability (Cronbach’s alpha > 0.60). Size number is 80 students. Data were analyzed using Pearson correlation, t-tests, and Analysis of Variance (ANOVA), with descriptive analysis following. The results show that most 10th-grade students at state senior high school 1 Turen have relatively low NEP scores, with an average score of 36.26, the lowest score of 27.00, and the highest score of 46.00. Demographic data also did not show significant differences, such as differences in class, gender, age, and blood type. The cause of the low environmental worldview among students is claimed to be the lack of learning that incorporates environmental worldview indicators at state senior high school 1 Turen.